Everything to lose - Gross, Andrew, 1952- (New York : William Morrow, 2014)
In the aftermath of Hurricane Sandy, Hilary Blum, a determined but down-on-her-luck single mother caring for a special needs son, becomes entangled in a murderous conspiracy to keep a twenty-year-old secret buried.
Keywords: Murder -- Investigation -- Fiction; Parents of developmentally disabled children -- Fiction; Extortion -- Fiction; Police -- New York (State) -- New York -- Fiction; Staten Island (New York, N.Y.) -- Fiction; Suspense fiction